Can Public Policy Increase Paternity Acknowledgment? Evidence from Earnings-Related Parental Leave - Anna Raute; Andrea Weber; Galina Zudenkova (Institute of Labor Economics (IZA), 2022)
A child's family structure is a fundamental determinant of future well-being, making it essential to understand how public policies affect the involvement of fathers. In this paper, we exploit a reform of the German parental leave system—which increased mother's income and reduced legal father's financial support burden—to measure the impact on the relationship contract choices of parents who were unmarried at conception. Based on detailed birth record data, we demonstrate that short-run reform incentives during the first period after birth nudge unmarried fathers into the long-term commitment of acknowledging paternity. This shift reduces single motherhood by 6% but leaves the share of marriages at birth constant. Moreover, the change in relationship contract choices is mostly driven by parents of boys. These findings are compatible with predictions from a model where parents choose between three types of relationship contracts based on the mother's and father's incomes and support obligations. Our results highlight the necessity of studying intermediate relationship contracts (i.e., between the extremes of marriage and single motherhood) to improve our understanding of potential risk groups among the rising number of children growing up outside of marriage.
Keywords: H42; I38; J12; J13; J16; J18; 330; paid parental leave; family structure; paternity establishment